Mereduksı Kecemasan Akademık Melaluı Konselıng Kelompok Teknık Relaksası - Ilmi, Yanal; Kiswantoro, Arista; Zamroni, Edris (Indonesian Journal of Educational Counseling, 2025)
The demands of competence felt by students at the vocational high school level make many vocational high school students feel academic anxiety. They are anxious because they feel that their abilities cannot meet all the standards held by vocational high schools. The objective to be achieved by implementing this research is to describe academic anxiety in students of SMK 2 Jepara after the application of group counseling with relaxation techniques. The type of research used is Guidance and Counseling Action Research. Data collection techniques: observation and interviews. Descriptive quantitative data analysis techniques. Academic anxiety in students has been successfully reduced. The condition of the research subjects has "Very High" academic anxiety with an average score of 89.73% in the pre-cycle period. Cycle I experienced a decrease of 66.11% with the "High" category. Continuing to cycle II experienced a decrease of 46.42% with the "Low" category.